Effect of udder type on udder traits, milk yield and some physicochemical characteristics of milk in Awassi ewes - Şeker, I; Köseman, A; Kul, S; Şeker, P; Koçyiğit, S (Journal of the Hellenic Veterinary Medical Society, 2022)
In this study, it was aimed to determine the effects of udder type on milk yield, udder and teat traits, and some physicochemical properties of milk in 54 Awassi ewe aged 3-4 years. In this study, Type-3 udder, which was reported to be prevalent in breeded Awassi ewes. Type-4, Type-5, and Type-6 udders were not detected in ewes. The lactation period, lactation, and the daily average milk yield values were calculated as 208.33 days, 138.59 liters, and 659.49 ml, respectively. The 90th day of lactation measurements were as follows: udder circumference (44.58 ± 0.51 cm), udder width (13.20 ± 0.36 cm), udder depth (17.66 ± 0.58 cm), udder volume (881.25 ± 37.41 ml), teat length-right (3.84 ± 0.15 cm), teat length-left (3.64 ± 0.17 cm), teat diameter-right (2.07 ± 0.14 cm). The values of the physicochemical characteristics of milk generally showed an increase from the beginning to the middle periods of lactation and then decreased. In conclusion, udder type had no significant effect on the lactation period, milk yield, udder and teat characteristics and the physicochemical properties of milk in Awassi ewes. New studies are required in the determination of the yield and other characteristics of ewes in Turkey.